1986
DOI: 10.1021/ma00162a020
|View full text |Cite
|
Sign up to set email alerts
|

Effect of electrostatic interaction on the liquid crystal phase transition in solutions of rodlike polyelectrolytes

Abstract: It is shown that the effect of electrostatic interactions on the liquid crystal phase transition in solutions of rodlike polyelectrolytes can be characterized by two parameters, one describing the increase of the effective diameter and the other the twisting action. The dependence of these parameters on the charge density and the salt concentration is studied both for weakly charged polyelectrolytes, for which the DebyeHucke1 approximation applies, and for highly charged polyelectrolytes, for which the full Po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
384
0

Year Published

1993
1993
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 347 publications
(399 citation statements)
references
References 22 publications
15
384
0
Order By: Relevance
“…Such models relied upon a highly salt-dependent charge density (22) inappropriately obtained from an effective-charge DH model (42)(43)(44)(45) valid only in the far field and not suitable for treating interactions between neighboring charges. This charge density was seemingly validated through experiments (20,21), but those studies were not conducted over a broad range of I and thus were not well suited to critically test salt-dependent effects.…”
Section: Discussionmentioning
confidence: 99%
“…Such models relied upon a highly salt-dependent charge density (22) inappropriately obtained from an effective-charge DH model (42)(43)(44)(45) valid only in the far field and not suitable for treating interactions between neighboring charges. This charge density was seemingly validated through experiments (20,21), but those studies were not conducted over a broad range of I and thus were not well suited to critically test salt-dependent effects.…”
Section: Discussionmentioning
confidence: 99%
“…Onsager (1949) already indicated that the effect of the electrostatic interaction will be equivalent to an increase of the effective diameter. Many years later Stroobants et al (1986) noted that this is not the only effect of the electrostatic interaction. The electrostatic repulsion depends on orientation and thus the effect of the electrostatic repulsion will be different in the isotropic phase from that in the nematic phase.…”
Section: Charged Rodsmentioning
confidence: 99%
“…The electrostatic repulsion depends on orientation and thus the effect of the electrostatic repulsion will be different in the isotropic phase from that in the nematic phase. In the remainder of this section we closely follow the treatment for charged rods given in Stroobants et al (1986).…”
Section: Charged Rodsmentioning
confidence: 99%
See 1 more Smart Citation
“…26 Another important aspect that needs to consider is the effects of charge and ionic strength that biopolymers carry in aqueous solution. [27][28][29] From a theoretical point of view, electrostatic interactions can cause the rods to twist away from the parallel configuration with respect to each other and increase the hardcore diameter to a larger effective one, while the persistence length increases as well. Nevertheless, the viscoelastic properties of LCP's have been studied quantitatively in considerable detail over the recent years.…”
Section: Introductionmentioning
confidence: 99%